Time-Referenced Effects of an Internal vs. External Focus of Attention on Muscular Activity and Compensatory Variability - Hossner, Ernst-Joachim; Ehrlenspiel, Felix (Frontiers in Psychology, 2010)
The paralysis-by-analysis phenomenon, i.e., attending to the execution of one’s movement impairs performance, has gathered a lot of attention over recent years (see Wulf, 2007, for a review). Explanations of this phenomenon, e.g., the hypotheses of constrained action (Wulf and colleagues, e.g., McNevin et al., 2003) or of step-by-step execution (Beilock et al., 2002; Masters, 1992), however, do not refer to the level of underlying mechanisms on the level of sensorimotor control. For this purpose, a “nodal-point hypothesis” is presented here with the core assumption that skilled motor behavior is internally based on sensorimotor chains of nodal points, that attending to intermediate nodal points leads to a muscular re-freezing of the motor system at exactly and exclusively these points in time, and that this re-freezing is accompanied by the disruption of compensatory processes, resulting in an overall decrease of motor performance. Two experiments, on lever sequencing and basketball free throws, respectively, are reported that successfully tested these time-referenced predictions, i.e., showing that muscular activity is selectively increased and compensatory variability selectively decreased at movement-related nodal points if these points are in the focus of attention.